Organisasi Mahasiswa: Sudah Tidak Relevan dan Tidak Penting Lagi? - Silalahi, Daniel; Asbari, Masduki; Faliza, Tengku Aisha (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to find out the importance of Student Organizations from different points of view. In this study report, a qualitative descriptive method was used by observing closely because the data source was obtained by listening to oral narratives from the Satu Persen - Indonesian Life School Youtube channel entitled "Student Organizations: Are They Not Selling?" which he explained. The results of this study explain the low interest of students in supporting organizations at their university. This research began with data on the decline in student interest in student organizations.